c-di-GMP Regulates Various Phenotypes and Insecticidal Activity of Gram-Positive Bacillus thuringiensis - Fu, Yang; Yu, Zhaoqing; Liu, Shu; Chen, Bo; Zhu, Li; Li, Zhou; Chou, Shan-Ho; He, Jin (Frontiers in Microbiology, 2018)
C-di-GMP has been well investigated to play significant roles in the physiology of many Gram-negative bacteria. However, its effect on Gram-positive bacteria is less known. In order to more understand the c-di-GMP functions in Gram-positive bacteria, we have carried out a detailed study on the c-di-GMP-metabolizing enzymes and their physiological functions in Bacillus thuringiensis, a Gram-positive entomopathogenic bacterium that has been applied as an insecticide successfully. We performed a systematic study on the ten putative c-di-GMP-synthesizing enzyme diguanylate cyclases (DGCs) and c-di-GMP-degrading enzyme phosphodiesterases (PDEs) in B. thuringiensis BMB171, and artificially elevated the intracellular c-di-GMP level in BMB171 by deleting one or more pde genes. We found increasing level of intracellular c-di-GMP exhibit similar activities as those in Gram-negative bacteria, including altered activities in cell motility, biofilm formation, and cell-cell aggregation. Unexpectedly, we additionally found a novel function exhibited by the increasing level of c-di-GMP to promote the insecticidal activity of this bacterium against Helicoverpa armigera. Through whole-genome transcriptome profile analyses, we found that 4.3% of the B. thuringiensis genes were differentially transcribed when c-di-GMP level was increased, and 77.3% of such gene products are involved in some regulatory pathways not reported in other bacteria to date. In summary, our study represents the first comprehensive report on the c-di-GMP-metabolizing enzymes, their effects on phenotypes, and the transcriptome mediated by c-di-GMP in an important Gram-positive bacterium.